2003
DOI: 10.1590/s0037-86822003000300004
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic effects on larval stages of Schistosoma mansoni during infection and re-infection of mice

Abstract: The sensitivity of the larval stages of Schistosoma mansoni to chemotherapy with praziquantel and oxamniquine was tested in mice during primary and secondary infections and after different intervals from cercarial exposure. Worm recovery by perfusion of the porto-mesenteric system, followed by counting and a morphometric study of the parasite, allowed the conclusion that the relative resistance of the larval stages of S. mansoni to schistosomicide drugs, demonstrated in primary infections, also persists when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…In areas with heavy transmission of schistosomiasis, it has been suggested that people might have been infected in the previous 3-5 weeks. Hence, such patients would harbor immature schistosomes that are less susceptible to PZQ [7,[39][40][41] . These immature stages have the high chance to survive a single treatment and mature to deposit eggs in the subsequent weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In areas with heavy transmission of schistosomiasis, it has been suggested that people might have been infected in the previous 3-5 weeks. Hence, such patients would harbor immature schistosomes that are less susceptible to PZQ [7,[39][40][41] . These immature stages have the high chance to survive a single treatment and mature to deposit eggs in the subsequent weeks.…”
Section: Discussionmentioning
confidence: 99%
“…For schistosomiasis, vaccine is nonexistent and drugs remain the mainstay of disease control. However, the current drug index is limited and/or inadequate, and the problem is being further exacerbated by the emergence of drug resistance (Ismail et al, 2002;Silva et al, 2003). This raises a need for complementary and alternative drugs that are both effective and safe.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, control of the disease by chemotherapeutic agents is impractical because of the common occurrence of reinfection after treatment (Silva et al 2003). In addition, control through molluscicides is costly and creates the problem of distributing and accumulating the applied chemical agents (Hamed 2010).…”
mentioning
confidence: 99%